APLIKASI SISTEM PENDUKUNG KEPUTUSAN DISTRIBUSI IKAN BERDASARKAN MODEL TRANSPORTASI DENGAN METODE VAM (STUDI KASUS: PT. KEMILAU BINTANG TIMUR) - Nining Suharyanti; Riswandi Ishak (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Sensitivity analysis is a way to determine the effect on the optimal solution generated by the simplex method if the parameter value is changed. Sistem is designed to address various areas of linear problems because it is open. However, before applying the linear problems encountered on the tool that has been created, it first needs to perform mathematical modeling of these problems. By utilizing this DSS, then all linear problems will be resolved properly and quickly. Optimization of transport models for the distribution of either cost minimization or profit maximization which is linear, the problem of transport carried out using the method of Vogel's Approximation Method (VAM). The method used to solve transportation problems by an efficient algorithm, but the variables are known with certainty. Ds for windows is one of the software for the optimal solution of transport problems that will assist in decision making for managers. The application of transport models used to determine the minimum cost of shipping goods from a supplier who happens to demand. Companies can save money and be more effective in the process of the optimal distribution of goods so it is easy to determine which potential buyers. Stages of the transport model begins with the initial results of the base feasible solution using the method of Vogel's Approximation Method (VAM) and ds software for windows which is a tool to help solve the optimization problem.